A qualitative study exploring the influence of uniform on pre-registration nurses views of self, professional identity and professional image. - Shaw, Kate (2009)
It is apparent from literature and from discussions with both students and registered nurses that uniforms have been, and continue to be, a hot topic. It is thought that uniforms hold personal significance for the wearer and act as powerful symbols representing the professions identity and image.